Endotoxemia is Associated with Renal Dysfunction in liver Transplantation Recipients during the First Postoperative Week - Yokoyama, Itsuo (1995)
The effect of endotoxemia on renal function was studied in 76 orthotopic liver transplant patients. In the preoperative period, a high preoperative serum creatinine level (>2.0 mg/dl) was significantly associated with postoperative endotoxemia. The serum total bilirubin level was significantly greater in the patients with high serum creatinine levels than in those with lower serum creatinine levels (<2.0 mg/dl). On the 7th postoperative day (POD), the serum creatinine level was significantly associated with an increased plasma endotoxin level. The serum total bilirubin and AST levels did not differ significantly between the patients with high and those with low serum creatinine levels. Based upon these data postoperative endotoxemia is suspected as being the principal cause of early postoperative renal dysfunction. A synergistic effect on renal function between cyclosporine and endotoxin may be important in the pathogenesis of the renal dysfunction seen after successful liver transplantation.